Pengaruh Terpaan Twit #UninstallBukalapak Terhadap Persepsi Netizen di Kota Denpasar (Studi Pada Perusahaan Bukalapak.com) - Sadyani Putri, Ni Made Mahindri; Pradipta, Ade Devia; Sugiarica Joni, I Dewa Ayu (E-Jurnal Medium, 2020)
ABSTRACT Bukalapak.com is one of the biggest unicorn in Indonesia, which has 50 million users. On 14th February 2019, CEO of Bukalapak tweeted that related with R&D (Research and Development). It caused hashtag #UninstallBukalapak appeared on Twitter. The aim of this research is to see how #UninstallBukalapak tweet affects the netizen's perception at Denpasar City. This research uses quantitative explanatory methods with social judgment and change of attitude theory. The data was analyzed by using simple linier regression analysis with SPSS 23. The results of this research show that the exposure of #UninstallBukalapak tweet caused the negative perception by netizen in Denpasar City, as much as 80%. But, netizen just give negative perception to Bukalapak.com company and they do not uninstall the application of Bukalapak.com in their smart phones. Keywords: Perception, Social Judgment and Change of Attitude, Twit Exposure, Twitter